Cultural diversity and local labour markets - Jens Suedekum; Katja Wolf; Uwe Blien (Institute for the Study of Labor (IZA), 2009)
During the last decade there have been marked changes in the composition of the non-native workforce in the German labour market. In particular there has been a notable increase in the diversity of nationalities of which the foreign workforce is composed. In this paper we investigate the effects of this diversity for native employees. Our analysis is conducted at the local level and uses a panel of 326 Western German regions over the time period 1995-2006. When considering high-skilled foreign workers, we find that both the size of this group and the diversification into different nationalities raise local wages and employment for native employees. For low-skilled foreign workers we find negative size effects. However, these negative effects can be partly offset if the group of low-skilled foreigners is culturally diversified. Our results imply that diversity raises productivity at the local level, but that it is important to distinguish the skill composition of the foreign workforce. These findings remain robust in a variety of robustness checks that take into account omitted variable bias, self-selection of foreigners into particular regions, and spatial autocorrelation.
Keywords: R23; J21; J31; 330; Regional labour markets; cultural diversity; immigration; spatial equilibrium; Regionaler Arbeitsmarkt; Regionale Lohnstruktur; Ausländische Arbeitskräfte; Kulturpsychologie; Interkulturelle Beziehungen; Deutschland